Ontology in the Poem of Atar Neyshaburi - Bahman Nozhat, Mohammad Khalilpoor, Fatemeh Modarresi, (Opción, 2019)
In this research, which has been conducted in a descriptive-analytical way, an important topic of ontology is to be explained in the transcendental thoughts of Attar. As a result, Atar looks at the world with a romantic attitude and his intellectual origin is verses and narratives, his ontology in three axes of God, the world and man is formed. In conclusion, Attar is one of the poets who, with the insights of love mysticism, have looked at being and ontology; his main idea in all his poetry collections is to explain the ontological issues of theology, worldview, and human beings.